2021
DOI: 10.3390/plants10050889
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Assessment of Moringa oleifera Leaves Extract against Oxidative-Stress-Induced Cytotoxicity in SHSY5Y Neuroblastoma Cells

Abstract: The current trend worldwide is searching plant extracts towards prevention of neurodegenerative disorders. This study aimed to investigate the neuroprotective effect of Alpinia galanga leaves (ALE), Alpinia galanga rhizomes (ARE), Vitis vinifera seeds (VSE), Moringa oleifera leaves (MLE), Panax ginseng leaves (PLE) and Panax ginseng rhizomes (PRE) ethanolic extracts on human neuroblastoma (SHSY5Y) cells. The 1-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging of VSE and MLE were 81% and 58%, respectively. Fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 68 publications
(42 reference statements)
4
6
0
1
Order By: Relevance
“…Oxidative stress is a major cause of neurodegenerative disease; thus, this inhibition is considered a promising strategy to prevent neurodegenerative disease. Ample evidence showed the potent antioxidant effect of M. oleifera in most of the parts of this plant ( 45 ), as previously described also elsewhere in human neuroblastoma (SH-SY5Y cell) ( 46 ). In this study, the TAC level in serum, which represented oxidative status in the brain, was analyzed; and found that both MOO and MOE failed to ameliorate the increased TAC serum levels in mice treated with Sco.…”
Section: Discussionsupporting
confidence: 67%
“…Oxidative stress is a major cause of neurodegenerative disease; thus, this inhibition is considered a promising strategy to prevent neurodegenerative disease. Ample evidence showed the potent antioxidant effect of M. oleifera in most of the parts of this plant ( 45 ), as previously described also elsewhere in human neuroblastoma (SH-SY5Y cell) ( 46 ). In this study, the TAC level in serum, which represented oxidative status in the brain, was analyzed; and found that both MOO and MOE failed to ameliorate the increased TAC serum levels in mice treated with Sco.…”
Section: Discussionsupporting
confidence: 67%
“…This study has observed the neuroprotective effect of the seed extracts in both stages of ischemic stages by the increase in animal survival rate, improved cognitive impairment, enhanced neuroplasticity, hippocampal neurogenesis, and cholinergic systems as also supported by a previous finding (Zhou et al, 2018). Hashim et al (2021) demonstrated that the ethanolic extracts of Alpinia galanga rhizomes (ARE), Panax ginseng leaves (PLE), Alpinia galanga leaves (ALE), M. oleifera leaves (MLE), Vitis vinifera seeds (VSE), and Panax ginseng rhizomes (PRE) were determined for their neuroprotective potential on human neuroblastoma (SHSY5Y) cells. MLE has an overall high reading of DPPH, FRAP, ROS scavenging, and nitro-blue tetrazolium (NBT) test via 2,7-dichlorodihydrofluorescein diacetate (DCFHDA) assay.…”
Section: Oleifera Extractssupporting
confidence: 84%
“… Hashim et al (2021) demonstrated that the ethanolic extracts of Alpinia galang a rhizomes (ARE), Panax ginseng leaves (PLE), Alpinia galanga leaves (ALE), M. oleifera leaves (MLE), Vitis vinifera seeds (VSE), and Panax ginseng rhizomes (PRE) were determined for their neuroprotective potential on human neuroblastoma (SHSY5Y) cells. MLE has an overall high reading of DPPH, FRAP, ROS scavenging, and nitro-blue tetrazolium (NBT) test via 2,7-dichlorodihydrofluorescein diacetate (DCFHDA) assay.…”
Section: Neuroprotective and Anti-neuroinflammatory Effects Of ...mentioning
confidence: 99%
“…In addition to interacting with proteins, polyphenols also have other activities, namely as antioxidants that function to ward off free radicals. Polyphenol compounds may be produced by the ethanol extract of A. galanga [19]. The ethanolic extract of A. galanga had a very high IC50 value against NIH-3T3 fibroblast cells.…”
Section: Resultsmentioning
confidence: 99%